Desain Pengembangan Kurikulum Pendidikan Agama Islam di SD Ditinjau Dari Faktor Psikologis - Linda, Linda (JPT : Jurnal Pendidikan Tematik, 2024)
The curriculum as a guide in achieving educational goals, has a central position as a determinant of the process and as an evaluation of the implementation of education. Curriculum development (Curriculum development / Curriculum design) as an advanced stage of coaching, namely activities that refer to produce a new curriculum. The psychological foundation as part of the main foundation in curriculum development has a strategic place in learning. However, curriculum development must be based on However, curriculum development must be based on assumptions derived from psychology which includes the study of what and how students develop, as well as how students learn. The main consideration when making policies on curriculum development should be knowledge of child psychology and how children learn. So that children do not become victims of the inability to understand the theory of child psychology in general.